The Analysis of the Islamic Community Member Engagement Based on Instagram Content Types - Nasuka, Moh; Wijaya, Tony; Hidayat, Anas; Muhamed, Nurul Aini (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
This study aims to determine differences in the level of Islamic community member engagement based on Instagram content types, namely photos, videos, and carousels. The results of this research are expected to contribute to social media users, especially Instagram, in determining the most appropriate types of content posts. This study is an ex post facto and uses secondary data from all posts of the most popular smartphone application-based Islamic community accounts in Indonesia, resulting in a total of 18,026 posts. Engagement rate is measured based on the number of likes and comments. Data is collected by documenting secondary data on Instagram. The sampling technique used was purposive sampling with the criteria of prioritizing new posts over old ones, considering that new posts tend to have a higher engagement; thus, the data will be more easily observed. The data analysis technique used is ANOVA. The findings demonstrated that there were notable distinctions in the number of likes and comments between photo posts and video posts, that photo posts had a higher degree of engagement than video posts, and that there were notable distinctions in the number of likes and comments between photo posts and carousel posts. Regarding likes and comments, photo posts receive more than carousel posts, and there is no difference between carousel posts and video posts; carousel posts and video posts receive the same amount of engagement. Based on the findings, it can be suggested that Islamic community managers pay attention to the choice of content type when uploading a post to an Instagram account to get optimal engagement. In addition, posting a single image often elicits more attention or engagement compared to video posts and carousels as well.